Retrospective effect of the matrimonial property agreement. Commentary of the judgment of Appeal Court of Murcia, 23th May 2018 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The judgment of the Appeal Court of Murcia, subject to comment, resolves a dispute faced by a couple in relation to the matrimonial property regime regarding a property acquired by the husband. Accordingly, the property must be registered under the property separation regime and be considered own property. According to the woman, the assets were acquired by the husband while the economic regime of the marriage was that of the common assets and, therefore, the assets should appear registered as common to both spouses. The element of discussion in the case is the granting of a marriage property agreement, celebrated four years after of the marriage, according to which the ma-rriage was contracted under community property. This is what the wife claims to hold that the property must be jointly owned. The husband, on the other hand, argues that the law applicable to the economic regime of the couple is Algerian law and, therefore, the separation of property. The Appeal Court of Murcia, without justifying the resolution of the case, establishes that, as in the matrimonial property agreement it is said that the marriage was celebrated under community property regime and the property was acquired before the granting of the same, the asset must to be considered common because it is not until the date of the matrimonial property agreement that the couple’s economic regime becomes that of patrimonial separation. With this solution, we study, fundamentally, the possible retroactive effects of matrimonial property agreements.
Keywords: matrimonial property regime; article 9.2 CC; article 9.3 CC; Regulation 2016/1103; non-retroactivity of matrimonial property agreement; registry advertising of the matrimonial property regime